Recurrent Pituicytoma in a Pediatric Patient: A Case Report - Maldonado-Morán, Miguel Ángel; Ospina, Jeisson; Vega, Juan; Restrepo, Claudia; Rico, Daniela; Zubieta, Camilo; Penagos, Pedro (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Pituicytoma is a rare tumor that arises from the glial cells of the neurohypophysis. For a long time, it was believed that pituicytomas only appeared in adults. Currently, at least three cases of this entity occurring in children have been reported in the literature. The aim of the present report is to describe the case of a 5-year-old girl who presented to the emergency department with visual disturbances, and the diagnosis was a recurrent pituicytoma. Therefore, the clinical presentation, the radiological features of the tumor, and the corresponding surgical management are described. Additionally, a brief review of the management of this unusual entity was performed.
Keywords: pituicytoma; pituitary tumor; pituitary stalk tumors; pediatric brain tumor